2007
DOI: 10.1093/hmg/ddm135
|View full text |Cite
|
Sign up to set email alerts
|

Association between variations in CAT and noise-induced hearing loss in two independent noise-exposed populations

Abstract: Noise-induced hearing loss (NIHL) is an important occupational hazard that results from an interaction between genetic and environmental factors. Although the environmental risk factors have been studied quite extensively, little is known about the genetic factors. On the basis of multiple studies, it was proposed that oxidative stress plays an important role in the development of NIHL. Here, we investigated whether variations (single nucleotide polymorphisms; SNPs) in the catalase gene (CAT), one of the genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 50 publications
3
59
1
4
Order By: Relevance
“…[14,15] In noise-induced hearing loss and idiopathic sudden hearing loss, investigating the effect of oxidative stress included studying various enzyme polymorphisms, and some relationships between the gene polymorphisms and the diseases were found. [16,17] In this study of CAT gene promoter region A/T polymorphism genotypes, we did not find a statistically significant difference between those with sensorineural hearing loss and a normal control group.…”
Section: Discussioncontrasting
confidence: 55%
“…[14,15] In noise-induced hearing loss and idiopathic sudden hearing loss, investigating the effect of oxidative stress included studying various enzyme polymorphisms, and some relationships between the gene polymorphisms and the diseases were found. [16,17] In this study of CAT gene promoter region A/T polymorphism genotypes, we did not find a statistically significant difference between those with sensorineural hearing loss and a normal control group.…”
Section: Discussioncontrasting
confidence: 55%
“…In former genetic studies on these noise-exposed workers, resistant and sensitive subjects were selected using a Z-score based on the ISO 1999 (ISO 1999 -International Organization for Standardization, 1990) 36 leading to a selection of 347 sensitive and 338 resistant subjects. 20 Age and noise exposure level in this initial selection were not equally distributed between resistant and sensitive workers. This resulted in significant effects of the interaction between age and noise exposure level and their quadratic effects.…”
Section: Subjectsmentioning
confidence: 87%
“…This renders HSP70 the second gene whose association with NIHL has been replicated in independent populations, besides CAT. 20 Replication in independent sample sets is crucial to confirm susceptibility genes for complex diseases. Our results indicate that HSP70 genes may be valid NIHL susceptibility genes as significant associations were observed in three independent populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, firm evidence for the involvement of genetic factors in human NIHL was limited. Konings et al found significant associations between CAT gene single nucleotide polymorphisms (SNPs) and susceptibility to NIHL (14). In Shen's experiment, individuals with GSTM1 null genotype had a statistically significantly increased risk of NIHL (OR =1.64) compared with those who carrying a wild-type GSTM1 genotype (15).…”
Section: Introductionmentioning
confidence: 99%